2004
DOI: 10.1074/jbc.c400010200
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 Initiates a Calcium Signal after Ligation by Intercellular Adhesion Molecule-1

Abstract: The MUC1 mucin is normally restricted to the apical surface of breast epithelial cells. In tumors, it is frequently overexpressed and underglycosylated. The MUC1 peptide core mediates firm adhesion of tumor cells to adjacent cells via binding to intercellular adhesion molecule-1 (ICAM-1). There is increasing evidence that MUC1 is involved in signaling, with current reports focusing on phosphorylation of the MUC1 cytoplasmic tail after indirect or artificial modes of stimulation. ICAM-1 is the only known direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 25 publications
(11 reference statements)
2
73
0
7
Order By: Relevance
“…This indicates that MUC1, although without intrinsic kinase activity (19), could function as a scaffold protein in signal transduction. Supporting this, we have shown that MUC1 can initiate an intracellular calcium signal in response to ICAM-1 ligation (20). Calcium-based signaling is frequently implicated in actin cytoskeletal ''treadmilling'' dynamics and cell migration (21).…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…This indicates that MUC1, although without intrinsic kinase activity (19), could function as a scaffold protein in signal transduction. Supporting this, we have shown that MUC1 can initiate an intracellular calcium signal in response to ICAM-1 ligation (20). Calcium-based signaling is frequently implicated in actin cytoskeletal ''treadmilling'' dynamics and cell migration (21).…”
Section: Introductionmentioning
confidence: 72%
“…The adaptor protein CrkL, as a downstream mediator of Src, plays a crucial role in the spatial-temporal regulation of Rho GTPase Rac1-Cdc42 activation and cell migration (30). Our previous work has shown that Src family kinase and PLC are involved in the MUC1/ICAM-1 interaction -initiated calcium signal (20). These findings suggest that CrkL may cooperate with Src in this MUC1/ICAM-1 interaction -induced actin cytoskeletal protrusive motility.…”
Section: Role Of Src Family Kinase Crkl and Plc In Muc1/icam-1 Intementioning
confidence: 92%
See 2 more Smart Citations
“…6 These features enable cs-mucins to provide a barrier function to mucosal pathogens by displaying sites for pathogen binding, acting as a releasable decoy, and sterically blocking binding of pathogens to underlying cellular receptors. The cytoplasmic tail domain of cs-mucins is highly conserved across species, undergoes both serine and tyrosine phosphorylation, and interacts with kinases and adaptor molecules, [7][8][9][10][11] consistent with a role in signal transduction in response to pathogen binding. As IAV specifically binds sialic acid-expressing receptors to trigger its entry by endocytosis into epithelial cells, the virus also has the potential to interact with sialic acid on cs-mucins, which may modulate both the infection process and the host response.…”
Section: Introductionmentioning
confidence: 99%